Observation of bound state self-interaction in a nano-eV atom collider. Issue 1 (December 2018) - Thomas, Ryan; Chilcott, Matthew; Tiesinga, Eite; Deb, Amita; Kjærgaard, Niels
Abstract Quantum mechanical scattering resonances for colliding particles occur when a continuum scattering state couples to a discrete bound state between them. The coupling also causes the bound state to interact with itself via the continuum and leads to a shift in the bound state energy, but, lacking knowledge of the bare bound state energy, measuring this self-energy via the resonance position has remained elusive. Here, we report on the direct observation of self-interaction by using a nano-eV atom collider to track the position of a magnetically-tunable Feshbach resonance through a parameter space spanned by energy and magnetic field. Our system of potassium and rubidium atoms displays a strongly non-monotonic resonance trajectory with an exceptionally large self-interaction energy arising from an interplay between the Feshbach bound state and a different, virtual bound state at a fixed energy near threshold. Self-interaction of a bound state through its coupling to the continuum is a phenomenon that is very difficult to observe. Here, the authors optically collide atomic clouds of rubidium and potassium to observe the self-interaction energy through precise measurements of magnetically tunable Feshbach resonances.